Evaluation of Democrat Party Voter Segmentation in Bandung City - Purnama, Aan Andi; Djatmiko , Budi (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
With the widespread idea that people are an aspect that needs to be considered and included in the political process, political parties are born automatically and grow to become candidates for the people and authorities. Political parties are usually considered the embodiment of a modern political system or the process of modernizing itself. This research uses qualitative research to produce descriptive data in interviews and written or verbal information from related people. Based on the sources, the number of Generation Y and Z voters in Bandung City for the 2024 Election is quite significant. According to the Bandung City KPU, as many as 53% of voters are millennials and Generation Z, totaling 1,872,381 voters. The KPU also noted that millennials dominated voters in the 2024 Election, reaching around 32.72%. This shows the crucial role of the young generation in the five-year contest.